Core Content for Wilderness Medicine Fellowship Training of Emergency Medicine Graduates. (17th January 2014) - Lipman, Grant S.; Weichenthal, Lori; Stuart Harris, N.; McIntosh, Scott E.; Cushing, Tracy; Caudell, Michael J.; Macias, Darryl J.; Weiss, Eric A.; Lemery, Jay; Ellis, Mark A.; Spano, Susanne; McDevitt, Marion; et al.
Abstract Wilderness medicine is the practice of resource‐limited medicine under austere conditions. In 2003, the first wilderness medicine fellowship was established, and as of March 2013, a total of 12 wilderness medicine fellowships exist. In 2009 the American College of Emergency Physicians Wilderness Medicine Section created a Fellowship Subcommittee and Taskforce to bring together fellowship directors, associate directors, and other interested stakeholders to research and develop a standardized curriculum and core content for emergency medicine (EM)‐based wilderness medicine fellowships. This paper describes the process and results of what became a 4‐year project to articulate a standardized curriculum for wilderness medicine fellowships. The final product specifies the minimum core content that should be covered during a 1‐year wilderness medicine fellowship. It also describes the structure, length, site, and program requirements for a wilderness medicine fellowship.